2010
DOI: 10.1111/j.1365-2834.2010.01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Generational differences in distress, attitudes and incivility among nurses

Abstract: Proactive initiatives to enhance the quality of collegiality can contribute to retention strategies. Building collegiality across generations can be especially useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 53 publications
(82 reference statements)
7
117
1
4
Order By: Relevance
“…Reio and Ghosh (2009) showed that young men were the most likely instigators of workplace incivility. Conversely, in other studies, reports have been issued of older perpetrators acting uncivilly toward younger colleagues who more often become the target of incivility (Leiter et al, 2010;Pearson & Porath, 2009). In relation to other demographic factors and their association with incivility, being part of an ethnic minority has been discussed as a risk factor for being treated uncivilly in the workplace (Cortina, 2008).…”
Section: Prevalence Of Incivilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Reio and Ghosh (2009) showed that young men were the most likely instigators of workplace incivility. Conversely, in other studies, reports have been issued of older perpetrators acting uncivilly toward younger colleagues who more often become the target of incivility (Leiter et al, 2010;Pearson & Porath, 2009). In relation to other demographic factors and their association with incivility, being part of an ethnic minority has been discussed as a risk factor for being treated uncivilly in the workplace (Cortina, 2008).…”
Section: Prevalence Of Incivilitymentioning
confidence: 99%
“…Cortina (2008) emphasizes the importance of understanding workplace incivility in combination with interpersonal relationships, in order to prevent and combat the processes that create discrimination, which circumvents the legislation in society. Selective incivility can in this context be seen as one of the barriers that prevent women, and ethnic minority groups, from reaching higher positions in society, according to Cortina. On the basis of the literature on risk groups of workplace incivility of Cortina et al (2002), Cortina (2008, Porath (2009), andLeiter et al (2010), we investigated which groups concerning gender, age, ethnicity, and power position are most targeted by workplace incivility and are more prone to act in an uncivil way.…”
Section: Prevalence Of Incivilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[3,27] More importantly, studies pointed out that the nurses' intent to leave their workplace and the subsequent organizational turnover are influenced more by supervisors than by co-workers, which can be due to the increased importance of mentoring in the nursing field. [10,28] Studies have also specifically discussed the importance of teams and collaboration at the workplace to motivate employees to stay with an organization or within the nursing profession. [29,30] 1.1.4 Work organizational factors Gardner et al reported that nurses who disagreed with staffing and scheduling in their units were more likely to leave their jobs.…”
Section: Social Work Environmentmentioning
confidence: 99%
“…The literature describes a myriad of relationships and mediating effects among variables related to turnover, such as generational diversity among the staff; the organizational climate; experience of workload, stress, and burnout; management style; perceptions of empowerment by nurses; different role perceptions; and individual factors including level of education and amount of nursing experience [2,15]. There is a need for longitudinal studies including both quantitative and qualitative approaches, to explore the values that influence both the nurses' intention to stay in their position and their decision to leave [2,16]. The need for in-depth research giving RNs the opportunity to explain in their own words has already been raised [15].…”
Section: Introductionmentioning
confidence: 99%